MANHAJ KRITIK MATAN ‘Ā’ISYAH RA - Niki Alma Febriana Fauzi (Muwazah, 2013)
Abstract : This paper discussed the methods used by ‘Ā’isyah as benchmark in criticizing matan hadith. The accusation against Islam about the lack of methodology in the study of hadith criticism, especially matan criticism, has forced contemporary Islamic scholars to create a method that can be used to criticize the substance of hadith. Indeed, the principles in criticized matan hadith have been made and used by ‘Ā’isyah. The ‘Ā’isyah manhaj of matan criticism has been tested the reliability. The writer concluded that the methodology of ‘Ā’isyah manhaj of matan criticism was proven reliable for tested the authenticity of hadith by used the correspondence of truth and coherence theories in philosophical epistemology as the method of analysis. Abstrak : Makalah ini membahas metode yang digunakan oleh 'Ā'isyah sebagai patokan dalam mengkritik matan hadis. Tuduhan terhadap Islam tentang kurangnya metodologi dalam studi kritik hadits, terutama kritik matan, telah memaksa ulama Islam kontemporer untuk menciptakan sebuah metode yang dapat digunakan untuk mengkritik substansi hadis. Memang, prinsip-prinsip dalam mengkritik hadits matan telah dibuat dan digunakan oleh 'Ā'isyah. The 'Ā'isyah manhaj kritik matan telah diuji reliabilitas. Penulis menyimpulkan bahwa metodologi 'Ā'isyah manhaj kritik matan terbukti dapat diandalkan untuk menguji keaslian hadits dengan menggunakan korespondensi kebenaran dan koherensi teori dalam epistemologi filsafat sebagai metode analisis.